318 One-step nucleic acid amplification (OSNA): a big 'step' towards a more accurate intra-operative assessment of sentinel lymph node status for early stage endometrial and cervical cancer?. (4th December 2020) - Tranoulis, Anastasios; Georgiou, Dimitra; Montalto, Stephen Attard; Yap, Jason; Twigg, Jeremy; Buruiana, Felicia; Sundar, Sudha; Balega, Janos; Singh, Kavita; Kehoe, Sean
Abstract : Introduction/Background: Sentinel lymph node (SLN) mapping is established as the standard of care for staging in selected cases of melanoma, breast and vulval cancer amongst other malignancies. Nonetheless, adapting its use in endometrial cancer (EC) and cervical cancer (CC) has been challenging. There is currently growing evidence to support its accuracy in early-stage EC and CC. One-step nucleic acid amplification (OSNA) has emerged as a rapid molecular assay for the detection of cytokeratin 19-mRNA in SLNs. The aim of the study was to ascertain the accuracy of OSNA in detecting SLN metastasis in early-stage EC and CC compared to that of histopathological ultra-staging. Methodology: A systematic search of MEDLINE, SCOPUS, ClinicalTrials.gov, and Cochrane Database was performed, spanning the period Jan 1975 to July 2020. Studies pertaining to the use of OSNA in detecting SLN metastasis in EC and CC were located. Pathologic ultra-staging was the reference standard. The quality of the included studies was assessed using the QUANDAS-2 tool. The DerSimonian-Laird random-effects model was used. Sensitivity, specificity, positive and negative likelihood ratio (LR+/LR-), diagnostic odds ratio (DOR), and the area under the curve (AUC) on SROC curve were calculated. We assessed the inter-study heterogeneity by the Higgin's I2 index. Statistical analysis was performed using the STATA version 16.1. Results: Five studies were included in the current analysis enrolling 223 women (191 with EC and 32 with CC) and 484 SLNs. The quality of the included studies was high. The number of the examined SLNs per patient ranged between one and five. The pooled sensitivity and specificity was 0.84 (95% CI 0.64 – 0.94, I2=34.59%) and 0.95 (95% 0.88 – 0.98, I2=87.58%), respectively. The pooled LR+ and LR- was 17.07 and 0.17, respectively. The pooled DOR was calculated 100.38 (95% CI 34.21 – 294.52, I2=85.24%). The SROC curve yielded an AUC of 0.95 (95% CI 0.93 – 0.97). Conclusion: The current evidence suggests that the OSNA assay is a useful and accurate technique for the intra-operative detection of SLN metastasis in early-stage EC and CC. The combined analysis using SLNs and OSNA assay is seemingly an attractive approach to tailor individualised management. The impact of micro-metastasis and isolated tumour cells on the prognosis of women with apparent early-stage EC and CC remains debatable and should be addressed in future research. As this evidence is preliminary, cross-institutional collaboration is warranted. Disclosures: Professor SK declares personal fees for consulting from Roche and Astra-Zeneca, outside the submitted work. The remaining authors certify that no party has a direct interest in the results of the research and that no benefit will be conferred to us or any organisation with which we are associated.